Reinhold Niebuhr's Approach to the State of Israel: The Ethical Promise and Theological Limits of Christian Realism - Moseley, Carys (Studies in Christian-Jewish Relations, 2011)
Reinhold Niebuhr’s support for the foundation of the state of Israel is argued to be an expression of his Christian realism, and as such is based on his ethics but not his theology. The first section assesses Niebuhr’s support for Jewish return to the Land of Israel in relation to modern protestant and Jewish support for relocation of the Promised Land back from America to British Mandate Palestine. The second section demonstrates that Niebuhr’s support for Zionism grew out of his threefold moral, political and theological realism. This meant taking into account Israel’s relation to the United States, and increasingly evidenced a national supersessionist outlook. The third section argues that this shift was undertaken via the role of the temporarily messianic nation, whereby the USA replaced Israel as a nation with a mission. In the fourth section, it is argued that the natural theology that underlies Niebuhr's ethics constitutes a 'Hebraic' turn which is ironic given that he does not ground his Zionism in the covenant with Abraham. The last section argues that Niebuhr’s support for Israel’s foundation needs to be understood within his reconstruction of natural law, along with his critique of the fusion of nationalism and religion in the Israeli-Palestinian conflict. As Niebuhr’s approach to Israel was based on ethics not dogmatic theology and exegesis, and as it became part of a notion of America as messianic, it failed to be passed on adequately to the mainline protestant churches.